EFFECT OF INTEGRATED NUTRIENT MANAGEMENT ON GROWTH, YIELD AND QUALITY OF STRAWBERRY (FRAGARIA × ANANASSA DUCH.)CV. SWEET CHARLIE - NIYATI JAIN; VIJAY BAHADUR; DEVI SINGH; PRATYUSH KUMAR (International Journal of Pharma and Bio Sciences, 2016)
The experiment conducted during the year 2013-14 and 2014-15 with 21 treatments included combinations of organic and microbial sources of nutrients (Compost, Poultry manure, Vermicompost, FYM, Azotobacter and PSB) replicated thrice with 18 plants per replication in Randomized Block Design. Observations were recorded for vegetative growth, fruit yield, and quality of fruit parameters. In different combinations organic manure and biofertilizers the treatment T15 (Vermicompost + Poultry manure +PSB +Azotobacter) was recorded highest plant height (16.19 cm), plant spread (24.68 cm), number of leaves plant-1 (15.79) and leaf area index (77.26 cm2) and T17 (Vermicompost+ FYM + PSB+ Azotobacter) was recorded highest petiole length (8.81cm). Plant supplied with T15 (Vermicompost + Poultry manure+ PSB+ Azotobacter) registered earliest in flowering (40.68 days) and T17 (Vermicompost+ FYM + PSB+ Azotobacter) highest number of flowers per plant (13.42). The maximum fruit weight (12.86 g), number of fruits plant-1 (11.78), quality TSS (7.05 °B) and Ascorbic acid (53.42 mg/100 g fruit pulp) and yield (112.63 g plant-1) were recorded with plants treated with a T15 (Vermicompost+ Poultry manure +PSB +Azotobacter) followed by T18 (Poultry manure+ compost+ PSB+ Azotobacter) and T17 (FYM+ Vermicompost + PSB+ Azotobater) treatment. the highest yield and best quality fruit were recorded in the combination of T15 (Vermicompost + Poultry manure+ PSB+ Azotobacter).